Intention to adopt and diffuse innovative ultraviolet light C system to control the growth of microorganisms in raw milk among Thais Dairy Farmers. (3rd May 2020) - Makarapong, David; Tantayanon, Supawan; Gowanit, Chupun; Inchaisri, Chaidate
Abstract: This research aims to investigate the factors affecting Thai dairy farmers' intention to use ultraviolet C technology (UV‐C) to reduce the number of microorganisms in raw milk. The researcher applied the innovation and diffusion theory (IDT) and the technology acceptance model 2 (TAM2) to evaluate dairy farmer's intention. The 477 dairy farmers in the central part of Thailand were interviewed using questionnaires. The collected data were analyzed using multinomial logistic regression (MLR). It was found that the intention to adopt UV‐C can accurately predict the factors affecting the intention to use the technology based on the intention levels to create diffusion and promote acceptance. To increase the diffusion and acceptance of UV‐C, the perceived usefulness to increase the milk price was the major influenced factor to promote technology acceptance. Providing facilities for maintenance, the use of this innovation and reporting news about the benefits of new technology to create positive attitudes and confidence lead to the spread of technology driven by early adopters. The technology developers should consider and design technology compatible with existing systems. However, the collaboration of all related parties is also needed to encourage Thai dairy farmers to try the new technology and observe the actual results.